Learning styles, preferences and needs of generation Z healthcare students: Scoping review. (November 2021) - Shorey, Shefaly; Chan, Valerie; Rajendran, Priyadharshni; Ang, Emily
Abstract: Aim: This scoping review aimed to consolidate evidence of the learning styles, preferences and needs of Generation (Gen) Z healthcare students. Background: It is essential to update the educational framework and pedagogy to meet each generation's distinct learning styles and preferences. Design: A scoping review of published and unpublished data. Methods: Six electronic databases (PubMed, Embase, CINAHL, PsycINFO, ProQuest and Scopus) were searched for studies written in English from June 2016 to July 2021. The Arksey and O'Malley (2005) five-stage framework was adopted to guide this review: (1) identifying the research question; (2) identifying relevant studies; (3) study selection; (4) charting the data; and (5) collating, summarising and reporting the results using a thematic analysis. Results: Seventeen studies were included and based on the thematic analysis, four themes were identified: (1) attributes of Gen Z healthcare students; (2) learning styles of Gen Z healthcare students; (3) learning preferences and needs of Gen Z healthcare students; and (4) teaching the Gen Z healthcare students: future directions and recommendations for educators. The findings implied more culturally diverse studies that adopt the mixed-methods or qualitative design are needed to capture deeper insights about Gen Z and in examining the effectiveness of technology integration and digital storytelling to boost students' learning and confidence in their future careers. Conclusions: Technology, campus resources and self-care strategies must be carefully integrated and planned to ensure an optimal and a safe learning environment for the students. The specific preferences and needs of the unique healthcare disciplines and educational subjects could be examined. A theory-based framework could be considered in designing future pedagogy. These future directions could allow educators to initiate vital change agents in guiding, supporting and nurturing students across generations.